Digital Literacy Education Among Students: Status, Pathways, and Implications in the Current Digital Era - Yi, Wang; Wang Siqian (Yayasan Nurul Yakin Bunga Tanjung, 2025)
This research aims to analyze in depth the digital literacy of students, which refers to their ability to effectively find, evaluate, create and communicate information using digital technology in the education and teaching process in higher education. In the digital age, digital literacy has become an essential and indispensable skill for personal, academic, and professional success. Cultivating digital literacy in university students is not only an important component of promoting the construction of higher education programs but also a crucial issue in facilitating the digital transformation of higher education. The study surveyed undergraduate students at Guizhou Normal University in Guiyang, China, using a structured questionnaire that covered six dimensions of digital literacy: information acquisition, communication and collaboration, digital content creation, security, privacy, and problem-solving. The results reveal that university students generally exhibit high levels of digital literacy, with no significant differences between genders. However, students from urban areas demonstrate significantly higher digital literacy levels compared to those from rural areas, particularly in security and privacy domains. The findings underscore the need for targeted interventions to enhance digital literacy in areas such as digital content creation and problem-solving. This study provides practical recommendations for higher education institutions to address these gaps and promote comprehensive digital literacy development among students especially in the fields of education and teaching